KONSEP MAKRIFAT MENURUT AL-GHAZALI DAN IBNU âARABI: SOLUSI ANTISIPATIF RADIKALISME KEAGAMAAN BERBASIS EPISTEMOLOGI - Dahlan, A. Zaini; Soeratno, Siti Chamamah; Sangidu, Sangidu; Mursyidi, Ahmad (Sekolah Pascasarjana UGM, 2013)
Al-Ghazali (1058-1111) is Sunni sufi representing Islamic mysticism and Ibnu Arabi (1165-1240) represents philosophical Sufism. Al- Ghazaliâs concept of Gnosis (knowing God) is based on the Quran and Hadith which is similar to its predecessor, al asyâari. In contrast, Ibnu Arabiâs concept of Gnosis is based on Greek philosophy and the school of Bathiniyah (Syiah). The fundamental difference between the two scholars is that Al-Ghazali is consistent with classical model of epistemological interpretation. He is very cautious in preventing understanding Islam (the sunni view) especially on aqidah (faith) from polytheism (musyrik) or infidelity (kafir). Meanwhile, Ibnu Arabi explores a variety of sources: Greek philosophy, school of shiâi Bathiniyah, and other sources with contempory interpretation paradigms whose characteristics are pluralistic, multicultural and universal, and gives more priority to welfare and justice. Even though the paradigm used by Al-Ghazali differs from the one employed by I bnu Arabi,they agree in some points. There are similarities in their paradigms and understandings. Al- Ghazali even justifies the righteousness of paradigm deployed by Ibnu arabi. Reflections of the two scholarsâ paradigms bear the main principles of mysticism. Al-Ghazali develops it with tahalli, takhalli, and tajalli, while Ibnu Arabi in addition to the three of Al Ghazali develops it with the teaching of wahdatul wujud.